Grain boundary energy, disordering energy and grain growth kinetics in nanocrystalline MgAl2O4 spinel. (1st May 2018) - Muche, Dereck N.F.; Marple, Maxwell A.T.; Sen, Sabyasachi; Castro, Ricardo H.R.
Abstract: An atomistic description and quantification of the individual contributions coming from the driving force and the grain boundary mobility to the phenomenon of grain growth can result in a better understanding and control of the microstructural evolution. The present work addresses these topics concerning nanocrystalline dense MgAl2 O4 . A systematic experimental investigation is performed on MgAl2 O4 spinel using Differential Scanning Calorimetry (DSC) to determine the grain boundary energy as function of the grain size ranging from ∼8  nm to ∼150  nm to quantify the thermodynamic driving force for grain growth. The grain boundary energy displays a strong dependence on the grain size along with additional increase in excess energy with decreasing grain size as a result of a size-induced cation site disorder (inversion). A grain growth study is performed at temperatures ranging from 1100 to 1300 °C in order to determine both grain boundary mobility and activation energy. The results demonstrate faster growth behavior for smaller grains that can be related to a combined increase in excess energies and grain boundary velocities with decreasing grain size. Graphical abstract: Image 1